Resilience as a Driver of Organizational Citizenship Behavior: An Empirical Study - Situmorang, Elis Fani; Elvinawanty, Rianda; Elizabeth Simanjuntak, Cinthya; Claudia Hotnauli Rumahorbo, Yolanda; Hartini, Sri (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
This research focuses on the importance of resilience in the context of Organizational Citizenship Behavior (OCB), which is increasingly relevant in today’s high-pressure work environments. The aim of this study is to examine the relationship between individual resilience and organizational citizenship behavior, as well as to explore the factors influencing these variables. This study employs a quantitative research method using a survey design, involving 115 respondents Belawan Type A Class I Navigation District. Data were collected using Likert scales to measure resilience and OCB, which were previously validated. The results reveal a significant positive relationship between resilience and organizational citizenship behavior. The findings suggest that individuals with higher resilience are more likely to engage in proactive behaviors, such as helping coworkers, showing initiative, and actively participating in organizational life. The implications of this research indicate that organizations should develop resilience training programs to enhance employee engagement, improve organizational culture, and boost overall performance.